Sustaining low pressure drop and homogeneous flow by adopting a fluidized bed biofilter treating gaseous toluene. (March 2022) - Lu, Lichao; Dong, Dong; Yeung, Marvin; Sun, Zhuqiu; Xi, Jinying
Abstract: A biofilter treating gaseous VOCs is usually a packed bed system which will encounter bed clogging problems with increased pressure drop and uneven gas flow in the filter bed. In this study, a lab-scale fluidized bed reactor (FBR) was set up treating gaseous toluene and compared with a packed bed reactor (PBR) with the same bed height of 150 cm. During 45 days of operation, the average elimination capacity of the FBR was 242 g m −3 ∙h −1, similar to that in the PBR (228 g m −3 ∙h −1 ) under an inlet toluene concentration of 100–300 mg m −3 and an empty bed residence time (EBRT) of 0.60 s. A better mass transfer was also confirmed in the FBR by molecular residence time distribution measurement. The pressure drop of the PBR increased dramatically and exceeded 8000 Pa m −1 while that of the FBR maintained approximately 200 Pa m −1 . On the 40th day, the air flow distribution in the FBR was more homogeneous than that in the PBR. The differences in pressure drop and air flow distribution were due to a much lower and more uniform distribution of biomass in the FBR than that in the PBR. The detached biomass collected from the off-gas of the FBR was almost 13 times of that from the PBR. Similar microbial community structures were observed in both systems, with the dominant bacterial genus Stenotrophomonas and the fungal genera Meyerozyma, Aspergillus . The results in this study demonstrated that the FBR could achieve a more stable performance than a PBR in long-term operation. Graphical abstract: Image 1 Highlights: The pressure drops in the fluidized bed was 17% of that in the packed bed. Homogenous flow distribution was achieved in the fluidized bed. Metabolic activity towards various carbon sources were improved in fluidized bed.